Impacts of ditch cleaning on hydrological processes in a drained peatland forest - Koivusalo, H.; Ahti, E.; Laurén, A.; Kokkonen, T.; Karvonen, T.; Nevalainen, R.; Finér, L. (HAL CCSD, 2008)
International audience One fourth (5.5 Mha) of forests in Finland are growing on peatlands that have been drained to improve forest growth. Forestry operations such as cuttings and ditch network maintenance in these areas may increase export of suspended solids and nutrients, and deteriorate water quality in receiving lakes and rivers. Mitigation of the deterioration calls for understanding how forest management operations affect peatland hydrology. A process-based simulation model FEMMA was applied to quantify the effects of ditch network maintenance on peatland water balance. The model has separate computation routines for evapotranspiration in tree stand and understorey vegetation, snow accumulation and melt, water movement in unsaturated and saturated soil, and drainage. Hydraulic characteristics of peat, as well as different drainage designs can be parameterised in the model. The model was applied in artificially delineated research catchments in northern Finland, where the ditch network was maintained by cleaning and digging the ditches deeper. The simulation results indicated that ditch cleaning affected the water balance slightly and the effect was dependent on stand characteristics and soil structure. When the growing stock volume was low and poorly conductive soil extended close to the soil surface, ditch cleaning increased evapotranspiration. In stands with a high stock volume and a thick topmost layer of highly conductive soil, evapotranspiration was less affected. In the study catchments, the effect of ditch cleaning on runoff was small compared to the error between measured and modelled runoff.